Graph Grammars for Knowledge Representation - Hess, Lilia; Mayoh, Brian H. (DAIMI Report Series, 1990)
This report consists of two papers presented at the March 1990 GRAGRA meeting in Bremen: the more general ''Representation of knowledge using graph grammars'' which argues for graphs as the universal KR formalism and the more specific ''The four musicians: analogies and expert systems -- a graphic approach'' which demonstrates the use of graphics for type inheritance and analogical reasoning.